Penerapan manajemen strategi bri dalam mengembangkan umkm melalui platform digital - Ainiyah, Rizka Nur (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze the implementation of BRI's strategic management in developing MSMEs through digital platforms and identify the role of BRI's digital strategy in supporting MSMEs. Thus, this research is expected to provide a clear picture of BRI's contribution in encouraging the progress of MSMEs in Indonesia through digital technology. This research uses a descriptive qualitative method using a literature review approach. This approach aims to explore in-depth information about BRI's digital strategy and how it contributes to the growth of MSMEs.BRI implements a digital strategy to support the development of MSMEs through several important stages. This strategy begins with formulation based on analysis of MSME needs and continues with the development of digital products such as BRISPOT, BRI Microfinance, and BRILink that facilitate access to financing and banking services. BRI also provides digital literacy training for MSMEs so that they can better utilize technology. BRI's implementation of the digital strategy has had a significant positive impact on the development of MSMEs. Through this strategy, MSMEs are able to expand market access, improve operational efficiency, and strengthen their competitiveness in facing business competition in the digital era. BRI's digitalization has proven to be a solution to the main challenges faced by MSMEs, especially in terms of access to financing and markets, which have been a major obstacle to their growth.